Croatian Latin Writers - an International Nationalist Phenomenon in a Socialist Republic - Jovanović, Neven, filolog (Array, 2013)
In Croatia, years between 1967 and 1971 saw the rise of a nationalist movement, both inside the Communist party and outside it. The movement, later known as the Croatian Spring or the MASPOK (short for “masovni pokret”, mass movement), was eventually suppressed by Josip Broz Tito and the rest of the Yugoslav communist leadership in 1971, with up to two thousand dissidents brought to trial, some of them sentenced to prison. Prominent figures from the Croatian Spring resurfaced as powerful players in the 1990s ; one of them was Franjo Tuđman (1922-1999), the controversial first president of the Republic of Croatia. Years leading to the Croatian Spring also saw publication of the first anthology of Latin writing in Croatia, Hrvatski latinisti - Croatici auctores qui Latine scripserunt (vols I-II, Zagreb 1969-1970), edited by Veljko Gortan (1907-1985) and Vladimir Vratović (1927), professors of the University of Zagreb. The anthology, comprising more than 1700 pages and bringing representative samples of thousand years of active literary use of Latin in all regions from which modern Croatia was formed, appeared as the highly symbolic second title in the series Pet stoljeća hrvatske književnosti (Five Centuries of Croatian Literature, published by Matica hrvatska in 180 volumes 1962-1995 ; first volume of the series was dedicated to Croatian medieval literature in Croatian). But actually attempts at systematic study and publication of Croatian Latin literary heritage in socialist Yugoslavia started even earlier, when, in the year 1951, the Yugoslav (later Croatian) Academy of Arts and Sciences introduced its series Hrvatski latinisti (Croatian Latin Writers, 11 vols 1951-2007). The undertaking received enthusiastic support by Miroslav Krleža (1893-1981), one of leading Croatian writers and prominent cultural and intellectual figures in Yugoslavia both before and after the World War II ; Krleža was the vice president of the Yugoslav Academy in 1948-1952, and he also publicly qualified Croatian Latin writers as “an inestimable proof that in this country the common sense of humanity did not capitulate even when the fates threw us into the darkest pit of history” (1953). From these facts springs the question that my paper will consider: did the study of the phenomenon of writing in Latin in Croatia (and by authors of Croatian origin) represent in socialist Yugoslavia a neutral undertaking, a covert nationalist operation, an acceptable response to this operation by the establishment, or an inherently ambiguous scholarly activity, splendidly isolated from everyday political struggles by the language that the writings were in? To better understand the context, an insight into teaching classical languages in Croatian schools is needed. There texts belonging to “Croatian Latinity” appear as prescribed readings in the gymnasium already in 1949, immediately after Tito broke with Stalin in 1948. Furthermore, we need to discuss the profile of works selected for the first volumes of Croatian Latin Writers series in 1952-1960, and analyse the presentation of Croatian Latin writers to the international community undertaken in the 1970s, which resulted in publication of the article by Gortan and Vratović “The basic characteristics of Croatian Latinity” (Humanistica Lovaniensia 20, 1971), and in a prominent place given to Croatia in 1977 in Jozef IJsewijn's Companion to Neo-Latin Studies (“Croatian Latin has a truly European importance”). All of these initiatives were seeds from which has grown the actual research of Croatian Latin writing, as well as the modern popular perception of Latin written in Croatia and by authors of Croatian origin as an important facet of Croatian cultural heritage, a facet where the national is blended with the international.